2020
DOI: 10.1371/journal.pone.0232431
|View full text |Cite|
|
Sign up to set email alerts
|

Angry, old, male – and trustworthy? How expressive and person voice characteristics shape listener trust

Abstract: This study examined how trustworthiness impressions depend on vocal expressive and person characteristics and how their dependence may be explained by acoustical profiles. Sentences spoken in a range of emotional and conversational expressions by 20 speakers differing in age and sex were presented to 80 age and sex matched listeners who rated speaker trustworthiness. Positive speaker valence but not arousal consistently predicted greater perceived trustworthiness. Additionally, voices from younger as compared … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 64 publications
(118 reference statements)
0
13
0
Order By: Relevance
“…The presence of such a hierarchy and possible interactions between different person characteristics may thus also explain more generally how overgeneralization effects of perceived gender, age, and beyond on trait or person perception may arise (Zebrowitz, 2011). For example, the rapid perception of a voice being female may restrict the relatively slower impressions of that person's trustworthiness to being relatively high (Schirmer et al, 2020; see also Lavan & McGettigan, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of such a hierarchy and possible interactions between different person characteristics may thus also explain more generally how overgeneralization effects of perceived gender, age, and beyond on trait or person perception may arise (Zebrowitz, 2011). For example, the rapid perception of a voice being female may restrict the relatively slower impressions of that person's trustworthiness to being relatively high (Schirmer et al, 2020; see also Lavan & McGettigan, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In a study on pitch and politics the authors conclude that “because women, on average, have higher-pitched voices than men, voice pitch could be a factor that contributes to fewer women holding leadership roles” ( Klofstad et al, 2012 ). Acoustic analysis has demonstrated that certain linguistic features are associated with trustworthiness, independent of attribution of a gender to the speaker, including “accelerated tempo, low harmonic-to-noise ratio, more shimmer, low fundamental frequency, more jitter, large intensity range” ( Schirmer et al, 2020 ). Physical bodily features also affect how a “credibility excess” or “credibility deficit” is attributed to interlocutors.…”
Section: Social Interpretationmentioning
confidence: 99%
“…features are associated with trustworthiness, independent of attribution of a gender to the speaker, including "accelerated tempo, low harmonic-to-noise ratio, more shimmer, low fundamental frequency, more jitter, large intensity range" (Schirmer et al, 2020). Physical bodily features also affect how a "credibility excess" or "credibility deficit" is attributed to interlocutors.…”
Section: Social Interpretationmentioning
confidence: 99%
“…Several studies have investigated the relationship between trust perception and speech [12][13][14][15][16]. In [12], voice models were evaluated to investigate the correlation between basic acoustical parameters and the perception of low and high trust.…”
Section: Related Workmentioning
confidence: 99%
“…Experiments conducted in [14] reported that low harmonicto-noise ratio, low mean fundamental frequency, and a fast speech rate are the most significant acoustic characteristics present in the perception of high trust. Additionally, tests comparing positive valence speakers against negative valence ones, younger voices against those with older voices, and female against male speakers showed that a higher perception of trust is achieved for positive valence speakers, younger voices, and female speakers, respectively.…”
Section: Related Workmentioning
confidence: 99%